Total Financing of Islamic Rural Banks and Regional Macroeconomic Factors: A Dynamic Panel Approach - Fakhrunnas, Faaza (Jurnal Ekonomi & Studi Pembangunan, 2020)
Islamic rural bank is a special purpose of Islamic banks, which finances Small and Medium Enterprises (SMEs) in Indonesia. This research aims to investigate a long-run relationship of the influence of regional inflation and economic growth on the total financing of Islamic rural banks in Indonesia. By adopting panel dynamics approach, this study utilized a biggest Islamic rural bank in each Indonesian province from 2013 to 2017 based on quarterly data, which consisted of 420 observation period. The result of this study exhibited that a long-run relationship existed among regional inflation and economic growth to the total financing of Islamic rural banks. Specifically, the long-run relationship also appeared in big size Islamic rural banks, although it was not in small and medium size Islamic rural banks. Variance decompositions and Impulse response factors analysis’ result explained that the majority of all regional macroeconomic variables contributed to the influence of total financing on the Islamic rural bank. The directions of its influence were different from each sample group. According to the results, Indonesian central bank must maintain inflation rate in the safety level for financial industry by following determined inflation target through appropriate monetary policies. This recommendation for the central bank is aimed to maintain and boost Islamic rural banks’ financing that will give benefits for financial industry in Indonesia.